Murder is no accident : - Prothrow-Stith, Deborah (Jossey-Bass, 2004)
Prothrow-Stith, a black female physician, and Spivak, a Jewish doctor, offer the strong message that violence is a preventable public-health problem. In part 1, they offer horrific statistics on violence among our youth and the recollections of people who have lost friends and relatives through gang violence, and analyze the "three waves" of the violence epidemic: first, among the inner-city poor; second, in rural and suburban areas; and third, involving girls dubbed "Rambettes." Part 2 explores some of the causes--including the violence portrayed on television and in video games--and the risk factors for particular juveniles. Part 3 focuses on the authors' creation of the first violence prevention program in the U.S. in 1983. Part 4 offers valuable lessons learned and advice on how to start similar programs to reduce the leading cause of death and disability among American children. This is a compelling look at youth violence and a valuable resource for parents, educators, and public-health practitioners.